Building climate-resilient urban communities through public space adaptation - Sakti, Gemilang Mohammad (Journal of Placemaking and Streetscape Design, 2025)
Background: Climate change poses critical challenges to urban communities, particularly in densely populated areas where the quality of life is highly vulnerable to environmental disruptions. This study aims to analyze the impacts of climate change on health, socio-economic, and environmental dimensions within urban neighborhoods while assessing the community’s adaptive capacity in responding to these challenges. Methods: A descriptive qualitative approach was employed through in-depth interviews, field observations, and analysis of secondary data from meteorological, statistical, and policy sources. Findings: The results reveal tangible consequences such as health risks from flooding and extreme heat, economic disruptions affecting small businesses, and environmental degradation that heightens disaster vulnerability. While public awareness of climate issues is relatively strong, adaptive capacity remains constrained by limited resources, insufficient climate education, and minimal participatory policy support. Conclusion: The study highlights the need for community-based adaptation strategies that integrate climate-sensitive urban design, enhanced climate literacy, participatory policy frameworks, and technology-driven innovations. Strengthening these aspects is crucial for fostering climate-resilient public spaces and promoting community well-being. Novelty/Originality of this article: Unlike studies that approach climate change from a broad regional perspective, this research emphasizes community-level resilience by integrating health, socio-economic, and environmental dimensions into the discourse of urban design and placemaking. The findings contribute context-specific strategies that bridge participatory planning, education, and technology with sustainable public space design to support low-carbon development and urban resilience.